Typifications of Andean Arenaria names (Caryophyllaceae), with a nomen novum - Montesinos-Tubée, Daniel B.; Iamonico, Duilio (Phytotaxa, 2023)
The nomenclature of the names Alsine weberbaueri, Arenaria musciformis, and Scleranthus peruvianus is investigated. The names were typified on specimens preserved at HOXA, MOL, and P. All these names are to be included in Arenaria. Concerning Alsine weberbaueri, a new combination (Arenaria weberbaueri) is proposed, whereas for Arenaria humboldtiana, a new name is provided for Scleranthus peruvianus since a previous Arenaria peruviana by Poeppig ex Rohrbach was validly published (Art. 53.1 of ICN).